2013
DOI: 10.2166/wst.2012.619
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of RO fouling in an integrated MBR/RO system for wastewater reuse

Abstract: Membrane filtration has gradually gained acceptance as the preferred pre-treatment for reverse osmosis (RO). In this paper, an integrated membrane bioreactor (MBR)/RO system for wastewater reuse treating real sewage water has been evaluated and the RO fouling has been characterised. The MBR achieved low values of organic matter, total nitrogen, PO(4)(3-), total organic carbon, turbidity and conductivity. Filtration with two different RO commercial membranes was performed after the MBR pre-treatment and the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Typically, in wastewater reclamation processes, the recovery levels of RO are 75 to 85% using two or more stages of RO in series (Wetterau et al, 2011). Although promising technologies are available to achieve over 90% of recovery, such as semi-batch RO process or known as closed circuit desalination (CCD) (Septon and Efraty, 2016;Warsinger et al, 2016;Werber et al, 2017), energy-efficient reverse osmosis (EERO) Chong Loo Fane et al, 2015), the practical recovery level is limited by membrane fouling, including inorganic scaling such as calcium phosphate, calcium carbonate and silica, organic fouling and biofouling (Antony et al, 2011;Kent et al, 2011;Moreno et al, 2013;Ridgway et al, 1984;Zhao et al, 2010). Usually antiscalants or disinfecting agents are added to RO feed water to reduce RO fouling, however, some…”
Section: Introductionmentioning
confidence: 99%
“…Typically, in wastewater reclamation processes, the recovery levels of RO are 75 to 85% using two or more stages of RO in series (Wetterau et al, 2011). Although promising technologies are available to achieve over 90% of recovery, such as semi-batch RO process or known as closed circuit desalination (CCD) (Septon and Efraty, 2016;Warsinger et al, 2016;Werber et al, 2017), energy-efficient reverse osmosis (EERO) Chong Loo Fane et al, 2015), the practical recovery level is limited by membrane fouling, including inorganic scaling such as calcium phosphate, calcium carbonate and silica, organic fouling and biofouling (Antony et al, 2011;Kent et al, 2011;Moreno et al, 2013;Ridgway et al, 1984;Zhao et al, 2010). Usually antiscalants or disinfecting agents are added to RO feed water to reduce RO fouling, however, some…”
Section: Introductionmentioning
confidence: 99%
“…a). The results suggest that the constituents of the fouling layer included proteins and polysaccharides . After water rinsing, the bands associated with organic fouling seem to decrease and the partial elimination of fouling permitted the characteristic peaks of the new membrane to appear (1095–1280 cm −1 ).…”
Section: Resultsmentioning
confidence: 92%
“…Soluble microbial products (SMPs) present in MBR permeate are found to be important constituents leading to RO membrane fouling [6]. The presence of inorganic salts in MBR permeate also leads to a reduction in RO permeate flux in MBR-RO systems for real domestic wastewater reuse [7] [8]. Jacob et al (2010) found that MBR effluent containing less concentrated organic matters and conductivity exhibits a lower reduction in RO permeate flux than more concentrated MBR effluent.…”
Section: Introductionmentioning
confidence: 99%